The unraveling of scientism : American philosophy at the end of the twentieth century - Margolis, Joseph, 1924- (Cornell University Press, 2003)
"The Unraveling of Scienticism centers on the primary commitment of analytic philosophy through the twentieth century to what Margolis calls "scientism"--The conviction that an unyielding reductionism, applied universally but in an exemplary way in the sciences, can provide a convincing account of the most important philosophical puzzles of the human world, those centered on the nature of the objective world, our knowledge of reality, language, and human existence. Margolis examines the principal puzzles that the analytic movement has addressed and argues that in recent years its claims have been effectively stalemated, perhaps even defeated."--Jacket